Neonatal testosterone voids sexually differentiated microglia morphology and behavior - Simões-Henriques, Carla Filipa; Rodrigues-Neves, A. Catarina; Sousa, Fábio J.; Gaspar, Rita; Almeida, Inês; Baptista, Filipa I.; Ambrósio, António F.; Gomes, Catarina A. (Frontiers in Endocrinology, 2023)
The involvement of immunity in psychiatric disorders, such as anxiety, is typified by the morphologic adaptation of microglia, immune cells of the brain, to anxiogenic stimuli. We previously reported sexually differentiated microglia morphology in adult rodents, in brain locations implicated in anxiety, including the pre-frontal cortex. These physiologic differences likely drive sex-dependent patterns of microglia morphologic remodeling in response to varied stress conditions in different periods of life, that correlate with sex-dependent behavioral adaptation to anxiogenic stimuli. The time-window of appearance of sex differences in microglia, correlating with sex-specific behavioral performance in anxiogenic conditions are still unknown. In rodents, a postnatal peak of the sexual hormone testosterone is determinant for the so-called brain masculinization and sex-determined behavioral traits. In the present work we aim to clarify if differences in microglia morphology are present at birth or can be driven by postnatal testosterone and impacts on the ability to deal with an anxiogenic context. Differences in microglia morphology are not present at birth, but are observable at adolescence (increased complexity of male microglia, particularly in branches more proximal to the soma), when differences in behavior are also observed. Our data also show that adolescent females neonatally treated with testosterone exhibit masculinized microglia and behavior. Importantly, between adolescence and adulthood, a sex-determined shift in the pattern of complexity takes place and microglia from females become more complex. When testosterone is administered, this morphological effect is partially abolished, approximating microglia and behavior to the male phenotype.